HEALTHCARE FAILURE MODE AND EFFECT ANALYSIS (HFMEA) PADA IDENTIFIKASI PASIEN PRIORITAS 1 DI INSTRALASI GAWAT DARURAT (IGD) RUMAH SAKIT WAVA HUSADA - Putri, Aryani Vindhya (Jurnal Administrasi Publik, 2024)
Healthcare Failure Mode and Effect Analysis (HFMEA) for Priority 1 Patients in Emergency Room Wava Husada Hospital. Emergency departments categorize Priority 1 (P1) patients as those requiring immediate attention due to conditions necessitating urgent resuscitation or surgery. Prompt and accurate identification of P1 patients is crucial for healthcare workers to prevent adverse events and ensure appropriate treatment. This study evaluates the efficacy of P1 patient identification processes in Hospital X's emergency room. A combination of Healthcare Failure Mode and Effects Analysis (HFMEA), focused group discussions, and process flow studies were utilized. The study found that P1 patients were often treated without identification bracelets, leading to potential mix-ups in examination documents and specimens. Although P1 patients are eventually issued identification bracelets within 5-20 minutes post-registration by family members, there's an evident need for an immediate, temporary identification protocol. Implementing such a procedure could enhance patient safety for P1 cases, but it requires ongoing monitoring and evaluation to ensure its effectiveness.